WHY ACCOUNTING? - Fagerberg, Dixon (The Accounting Review, 1957)
The attractive qualities of accounting as a study and as an applied art greatly appeal to many people. It follows that the student about to decide on a career should be told about some of accounting's often overlooked attractions and some of the seldom-mentioned personal characteristics of the men and women who professionally practice it. In the realm of intellectual endeavor, the same thing is true of accounting to a far greater degree than the uninitiated ever realize. In almost all fields of performance, successively greater achievement is closely inter-related with measurement. Mount Everest was climbed because it was there as a challenge. In a sense, records are broken because the measurements are there. Man is the animal that measures and compares. Although professional accountants and professional management are mindful of it, the laity has little conception of the fact that without accounting the nation's business could not possibly be organized on its present scale. Like athletes or teachers or doctors or ministers, no two accountants are alike. They differ in their grasp, their depth, their approach, their thinking, theft mode of expression.